Genetic, Endocrine, and Microbiological Assessments of Blue, Humpback and Killer Whale Health using Unoccupied Aerial Systems. (24th December 2021) - Atkinson, Shannon; Rogan, Andrew; Baker, C. Scott; Dagdag, Ralf; Redlinger, Matthew; Polinski, Jennifer; Urban, Jorge; Sremba, Angie; Branson, Maile; Mashburn, Kendall; Pallin, Logan; Klink, Amy; et al.
ABSTRACT: Unoccupied aerial system (UAS) technologies applied to health assessments of large whales can have positive implications for progressive management. We focused on the collection of cetacean respiratory blow samples for endocrine, DNA profiling, microbial metabarcoding, and metagenomics analyses, with the goal of improving management of large whale populations. Blow samples were collected from humpback ( Megaptera novaeangliae, n  = 109 samples analyzed), blue ( Balaenoptera musculus, n  = 21 samples analyzed), and killer whale ( Orcinus orca, n  = 1 sample analyzed) species, as well as the responses of the whales to the collection of their blow by UAS. Endocrine analyses were validated for 5 steroid hormones in humpback whales and 4 hormones in blue whales. For DNA profiling, we attempted to extract and amplify nuclear and mitochondrial DNA, resulting in sequencing of mtDNA haplotypes for 54% of samples, identification of sex for 39%, and individual identification by microsatellite genotyping for 17%. The DNA profiles of 2 of the blow samples from humpback whales were matched to a DNA register for this regional population. Metagenomic and microbial metabarcoding classifications found a diverse number of bacteria, eukaryotes, and viruses in humpback whale blow. Although a significant portion of classifications were found in both seawater and blow, several of the most abundant organisms were present only in blow samples, suggesting they are true members of the respiratory microbiome. A comprehensive integration of laboratory‐based approaches using noninvasive UAS collection technologies could become an important management tool for health assessments of large cetaceans, especially for species listed as endangered. The addition of individual and population‐level health assessments to currently practiced stewardship of large whales, renders them as excellent sentinels of ocean health. © 2021 The Wildlife Society. Abstract : Unoccupied aerial system (UAS) technologies were used to collect respiratory blow samples from large whales for endocrine, DNA profiling, microbial metabarcoding, and metagenomics analyses. We demonstrate how UAS applied to health assessments of humpback, blue, and killer whales can have positive implications for improving cetacean management. Abstract :